Liminal and the invisible: trauma and the human trafficking survivor in the UK - McNamara, Mei-Ling Jung (The University of Edinburgh, 2018)
In the last decade, Britain has become a destination state for traffickers and a fertile ground for forced labour practices. It has seen a dramatic rise in transnational criminal gangs targeting the most impoverished and vulnerable migrant populations who provide cheap labour to Britain’s industries. The UK government estimates that there are 10,000-13,000 potential victims of slavery in the UK. Victims are targets for criminalisation by the gangs that exploit them and the authorities that seek their removal. Yet very few people have been prosecuted in Britain for labour trafficking crimes and few victims have received compensation in UK employment courts. Much more common are the arrests, convictions and deportations of the workers themselves. This thesis applies the concept of liminality – used historically to describe different states of ritual in traditional societies – to the experience of the trafficked individual, analysing how periods of uncertainty and shifting roles of identity can make victims targets of predatory traffickers. Next, it looks at the extent of modern-slavery and human trafficking in the U.K. today, while arguing that trafficked victims can also be made increasingly vulnerable by the processes of protracted judicial procedures that prioritise an individual’s immigration status over safeguarding them from future harm. While victims should be afforded human rights protections under national and international anti-trafficking laws, it argues that certain measures are not consistently applied which means that victims can be left doubly traumatised, putting them at risk of criminalisation by both perpetrators and state structures. Drawing from primary case studies, it looks at how trafficked victims can be confined to marginal spaces within British society, barring them from legal and political rights and ignoring their psychological and social welfare – creating conditions for further exploitative labour. Furthermore, it discusses the impact trauma has on human trafficking victims, and what implications this has on testimony, memory and identity. It analyses how trauma and the resulting structures of power that process individuals after their exploitation can create and exacerbate states of liminality for survivors, creating vulnerable states of ‘non-being’ that further raise questions of agency, control and criminalisation. Finally, there is a discussion regarding how documentary film might highlight the hidden human rights abuses that exist in slavery today. Documentary film also carries with it a responsibility not to re-traumatise survivors and it is through the discussion of ethics with vulnerable subjects that the issue of filming victims of human trafficking is highlighted. Through theoretical research, case studies and semi-structured interviews, this trans-disciplinary work examines this issue in discussions of human rights, labour law, criminal justice, psychological trauma and documentary ethics. This thesis therefore has implications for the status of human trafficking victims, through its analysis that reveals the psycho-spatial experience of survivors, and the structures and practices that increase vulnerability and possible re-exploitation.
Keywords: human trafficking; trauma; liminality